Chemical Composition of Leaf Essential Oil of Psidium guajava L. from North East India. Issue 1 (2nd January 2019) - Borah, Angana; Pandey, Sudin Kumar; Haldar, Saikat; Lal, Mohan
Abstract: Psidium guajava L. (commonly known as guava) is a small tree belonging to the family Myrtaceae. It grows well in the tropical and subtropical regions of the world. It has been used in traditional medicine since a long time. The different parts of the plant like bark, leaves and fruit, is used to cure skin ailments, stomach ache, indigestion, anti-inflammatory, diabetes, hypertension, wounds, pain relief, cough, rheumatic pain and various other ailments. The chemical composition of the whole guava tree renders it the medicinal properties. The chemical composition of the essential oil extracted from the leaves of P. guajava, from North East India, was identified in this study. The leaves yielded 0.51 % (v/w) essential oil. Although there are many reports on the chemical composition of its leaf essential oil; there is no report available in the public domain of the chemical composition of Psidium guajava from North East India. Therefore, the leaves of the P. guajava collected from North East India were hydro-distilled and chemical compounds were identified using GC/MS. A total of 27 compounds were identified in the leaf essential oil. The major compounds were α-terpinyl acetate (23.57 %), trans-caryophyllene (17.65 %), nerolidol (12.16 %), α-cadinol (6.71 %), α-copaene (6.5 %) and minor compounds identified were α-humulene (3.92 %) and (-)-caryphyllene oxide (3.66 %).